20 Proteomics of human plasma in diastolic heart failure (DHF) using novel chemical affinity, mixed mode matrix (M3). (17th November 2015) - Mbasu, Richard J; Hakimi, Amirmansoor; Sandhu, Jatinderpal K; Heaney, Liam M; Quinn, Paulene A; Bhandari, Sanjay S; Jones, Donald JL; Ng, Leong L
Abstract : Background: The understanding of diastolic heart failure (DHF) has developed in recent years, a condition that was often misdiagnosed for systolic heart failure (SHF). Although there are constant advances in diagnostic technologies, treatment and diagnosis for DHF still remain a challenge prompting a need for biomarker discovery within human plasma. Prospecting for new protein biomarkers can be hindered by the presence of high abundant proteins (HAPs), masking the appearance of potentially diagnostic low abundance proteins (LAPs) due to their dominance in the sample matrix. A novel method, termed Mixed Mode Matrix (M3), is described to reduce the complexity and improve the dynamic range of plasma proteomics to investigate biomarkers in DHF. A pilot study involving controls (n = 10) and disease (DHF n = 10, SHF n = 10) plasma was carried out. Method: HAPs were depleted using MARS14 column, bound to M3, eluted into fractions using increasing concentrations of NaH2 PO4 and purified by solid-phase-extraction. A BCA protein assay was used to determine protein concentration prior to digestion. Peptides were separated using high-resolution liquid-chromatography (nano-UPLC) and high-definition-MSE analysis. Results: A method for LAPs enrichment was developed. Over 300 LAPs were identified with 1% false discovery rate and contained at least 2 identified peptides. In depleting and enriching plasma with M3, we are able to expand the dynamic range of plasma thus enabling us to identify the LAPs. Conclusion: M3 has the potential to improve efficiency and cost-effectiveness of LAPs enrichment, leading to plasma protein biomarker identification for diagnosis and treatment of a multitude of disease states.